PENGARUH PEMUPUKAN SUSULAN TERHADAP KUALITAS MEDIA DAN PROSES BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) PADA TAMBAK TRADISIONAL PLU - BOBY DANI DARMAWAN (Akuatik: Jurnal Sumberdaya Perairan, 2008)
White leg shrimp is one of 110 Penaeid species which have more profitable chances to cultivate. These shrimp could produce 10 – 20 tons per Ha compare with tiger prawn that only produce 2 – 5 tons per Ha. White leg shrimp could be harvested less than 120 days, and it more resist to the disease, not only that, the other advantages of these shrimp was its habit that live at all over the teritorial of the media so that it can be cultivate with higher density. The optimal result or product from brackishwater pond cultivation is according to how the technical nursery was done. Water quality was the most important point that must be checked and controled to gain the optimal production. The following fertilization was an alternative way to stabilize the water quality especially in traditional pond. This manner could make the bio-organism such as fitoplankton and benthos as white leg shrimp’s natural food grow continously. The study was done with four different doses of the following fertilization (2,5%, 5%, 7,5%, and 10% from forward fertilization). After 86 days rearing period, the best following fertilization shown with the dose 5% from forward fertilization. Water quality such pH, ammonium, sulfic acid and dissolved oxygen with this manner reached the best condition and significantly different from the other (p<0,05 for dissolved oxygen and sulfic acid; and p<0,01 for pH and ammonium). In spite of the water quality, the pond with 5% following fertilization got the best result of harvesting. This manner had the greatest biomass, and average body weight and was high significantly different from the other (p<0,01) The survival rate was got the highest mark although its not significantly different from the test (74,147%) and so as the average daily growth (0,194 gr per day).